Chaos in the Shimizu-Morioka Model With Fractional Order - Wei, Zhangzhi; Zhang, Xin (Frontiers in Physics, 2021)
The investigation of dynamical behaviors for fractional-order chaotic systems is a new trend recently. This article is numerically concerned with the Shimizu-Morioka model with a fractional order. We find that chaos exists in the fractional-order model with order less than three by utilizing the fractional calculus techniques, and some phase diagrams are also constructed.